Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Dengan Komitmen Organisasi Sebagai Variabel Moderating Pada Rumah Sakit Pekanbaru - kamilah, faizah (Jurnal Daya Saing, 2016)
Abstract: This study was conducted using a survey method to Hospitals in the city of Pekanbaru. This study aims to examine the effect of budget participation on managerial performance and organizational commitment as moderating variable in the hospital in Pekanbaru. The population in this study was 21 Hospital in Pekanbaru. Data collected by distributing questionnaires to 84 respondents, but only 80 questionnaires that can be used in this study. The type of data used are primary data to the data collection method using a questionnaire. Data analysis method used in this study is multiple regression (multiple regression). These results indicate that the effect of budget participation on managerial performance with 0.002 significance (alpha 0.05). Organizational commitment can moderate the effect of budget participation on managerial performance with a significance of 0.000 (alpha 0.05). Keywords: Budget Participation, Organizational Commitment, Manajerial Performance.